PENGEMBANGAN APLIKASI DKM REGISTRATION SYSTEM BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Muhamad Adillah Fatih; Reza Arif Maulana; Rizki Reza Pratama; Muhammad Darwis; Retno Hendrowati (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2024)
The Mosque Family Council (DKM) Paramadina regularly holds various events or activities such as the Prophet Muhammad's Maulid event, Qurban, to the Religious Festival. One of the problems often faced by DKM Paramadina is that registration and attendance data are not synchronized, making it difficult to ensure that participants are entitled to event benefits. To overcome this problem, DKM Paramadina needs an effective and efficient registration and attendance system in ensuring data consistency. The purpose of this study is to improve and develop an event registration and attendance recording system using the Waterfall Method approach. The result of this study is a web-based DKM Registration System, which allows the use of recording and monitoring the attendance of event participants efficiently. This system utilizes Next.js Framework for Frontend, Express.js for Backend, and Node.js as runtime. To store registration and attendance data, this system is integrated with Google Spreadsheet by utilizing Google Application Programming Interface (API). In addition, Node Mailer is also used to send a QR Code to the registrant's email for attendance. The Blackbox method has been used to test the effectiveness of the DKM Registration System and the results show good performance. This research provides a solution to overcome conventional problems in data management, ensuring registration and attendance data remain synchronized and consistent.